Reflexões acerca das racionalidades em unidades de conservação: o caso do Refúgio de Vida Silvestre dos Campos de Palmas - Strapazzon, Marcia Casarin (2015)
At one point it is evident that contemporary environmental problems are the result of human activities and have social origin, rooted in the dominant thought system. Thus, instruments are created - protected areas - to protect nature of human action. In Brazil, this instrument was made official by the Sistema Nacional de Unidades de Conservação, which created 12 categories of protected areas, divided into two groups, full protection and sustainable use. This study aimed to analyze a particular category of protected area, the Wildlife Refuge. This category belongs to the group of strictly protected areas of nature (is allowed only indirect use), but can consist of private property. Thus, toured the historical creation of the Sistema Nacional de Unidades de Conservação, investigating, in that context, the origins of the category. It was observed that, accidentally or not, the Wildlife Refuge category has an unprecedented configuration, and in front of the current environmental panorama, which entails a paradigm shift, may prove appropriate and feasible. The category analysis led to reflection on the situation of the owners whose lands are covered by such conservation unit, which face a confrontation of rationalities - an environmental rationality is imposed on the dominant rationality, instrumental/economical because protected areas bring restrictions on productive activities that may harm the expectation of increasing economic gains. In the light of contemporary theories that address the environmental issue, it might be inferred that, in general, it is expected that these people in order to match your needs with the objectives of protection advocated by the conservation unit, take advantage of this new situation. That is, take hold of their capacity to greening its activities, but within the dominant rationality. Theoretically, there are alternatives to this trend, however are deeper, requiring the transformation of dominant rationality, which can be considered the root of the ecological crisis of today. From a broader analysis get to to narrower aspects, until the analysis of a specific Wildlife Refuge, the Refúgio de Vida Silvestre dos Campos de Palmas, in Paraná. For this, it was characterized the region where the unit was created and therefore the historical context that shaped an ecosystem over time so that now deserved (or needed) to be protected. Through an desing inspired on the theoretical and methodological approach of the theory of translation, the process of creating the RVS-CP was described and analyzed, demonstrating the socio-technical network formed symmetrically by human and non-human actors in this process, and seeking to identify how they act, their demands, their negotiations and action tools. Finally, we come to the real life of those people whose properties are included in the Refúgio de Vida Silvestre dos Campos de Palmas. At this point the research focused on a search to consider both elements of economic rationality and substantive rationality. Considering the rationalities confrontation from the creation of the UC, it was observed that although usually relegated to the background, immaterial things of life have crucial role in the objectives of respondents owners. And the livelihood strategies of these families follow the trends of transformation that occurred in recent decades in rural areas, strongly marked by the combination of agricultural and non-agricultural incomes.